Legal harmonization, institutional quality, and countries' external positions: A sectoral analysis - Franziska Bremus; Tatsiana Kliatskova (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper analyzes links between institutional harmonization and bilateral portfolio debt and equity holdings at the sectoral level. Motivated by the action plan for the European Capital Markets Union, we examine the potential for legal harmonization and convergence in institutional quality to affect financial structures. Our analysis yields three key insights. First, legal harmonization across the EU promotes capital market integration via increased portfolio equity holdings. Second, discrepancies in institutional quality matter for cross-border portfolio positions: economic agents increase their portfolio debt investment in countries that are transparent and have efficient insolvency procedures, investor protection, and tax systems as compared to the domestic ones. Third, the relationship between external capital holdings and institutional harmonization varies significantly across sectors. The other financial corporations sector, which accounts for a large share of portfolio positions, tends to react more to institutional harmonization than do banks and the non-financial private sector.
Keywords: E02; F21; G15; 330; capital market integration; legal harmonization; sectoral effects